2021
DOI: 10.1177/15589447211003177
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid Nonunion Is a Disabling Problem in a Military Population

Abstract: Background Scaphoid nonunion can occur in up to 55% of displaced scaphoid fractures. Long-term functional outcomes of this injury are lacking. In addition, no study has published rate of return to active military service after this injury. Our goal was to educate providers and patients on expected functional outcomes and return to duty after treatment of scaphoid nonunion. Methods We conducted a retrospective review of patients who underwent scaphoid nonunion repair at our institution from 2008 to 2017. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although her corrective osteotomy was uneventful, multiple studies have shown poorer results with delayed fracture care and delayed traumatic care as well. 3 4 Additionally, delayed nerve and tendon repair, as experienced by patient 3 in this cohort, could also lead to poorer long-term outcomes. 13 14…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although her corrective osteotomy was uneventful, multiple studies have shown poorer results with delayed fracture care and delayed traumatic care as well. 3 4 Additionally, delayed nerve and tendon repair, as experienced by patient 3 in this cohort, could also lead to poorer long-term outcomes. 13 14…”
Section: Discussionmentioning
confidence: 97%
“…Although her corrective osteotomy was uneventful, multiple studies have shown poorer results with delayed fracture care and delayed traumatic care as well. 3,4 Additionally, delayed nerve and tendon repair, as experienced by patient 3 in this cohort, could also lead to poorer long-term outcomes. 13,14 A paucity of data exists with regard to severity of symptoms and perioperative risk, as most studies report on a heterogeneous population, with a variety of procedures, with and without symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 6 found osteoarthritis in 56% of the nonunion cases after 36 years compared with 2% of the healed fractures. More and more attention was paid to nonunion of scaphoid fracture because it could decrease the function of the wrist and greatly affect the patients' life quality 7 , 8 , 9 . The nonunion rate of scaphoid fracture in the literature was 10%–40% 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%